Cerebral Autoregulation in Non-Brain Injured Patients: A Systematic Review - Longhitano, Yaroslava; Iannuzzi, Francesca; Bonatti, Giulia; Zanza, Christian; Messina, Antonio; Godoy, Daniel; Dabrowski, Wojciech; Xiuyun, Li; Czosnyka, Marek; Pelosi, Paolo; Badenes, Rafael; Robba, Chiara (Frontiers in Neurology, 2021)
Introduction: Cerebral autoregulation (CA) plays a fundamental role in the maintenance of adequate cerebral blood flow (CBF). CA monitoring, through direct and indirect techniques, may guide an appropriate therapeutic approach aimed at improving CBF and reducing neurological complications; so far, the role of CA has been investigated mainly in brain-injured patients. The aim of this systematic review is to investigate the role of CA in non-brain injured patients. Methods: A systematic consultation of literature was carried out. Search terms included: “cerebral autoregulation AND sepsis”, “cerebral autoregulation AND surgery”, “cerebral autoregulation AND non-brain injury”. Results: Our research individualized 294 studies and after screening, 22 studies were analyzed in this review. Studies were divided in three groups: CA in sepsis and septic shock, CA during surgery, and CA in the pediatric population. Studies in sepsis and intraoperative setting highlighted a relationship between the incidence of Sepsis-Associated Delirium and impaired CA. The most investigated setting in pediatric population is cardiac surgery but the role and measurement of CA needs to be further elucidated. Conclusions: In non-brain injured patients, impaired CA may result in cognitive dysfunction, neurological damage, worst outcome and increased mortality. Monitoring CA might be a useful tool for the bedside optimization and individualization of the clinical management in this group of patients.